Structure of an ABC transporter solute‐binding protein specific for the amino sugars glucosamine and galactosamine. Issue 6 (1st June 2016) - Yadava, Umesh; Vetting, Matthew W.; Al Obaidi, Nawar; Carter, Michael S.; Gerlt, John A.; Almo, Steven C.
Abstract : A solute‐binding protein from Pfam13407 was found to be specific ford ‐glucosamine/d ‐galactosamine by differential scanning fluorimetry and X‐ray crystallography. Abstract : The uptake of exogenous solutes by prokaryotes is mediated by transport systems embedded in the plasma membrane. In many cases, a solute‐binding protein (SBP) is utilized to bind ligands with high affinity and deliver them to the membrane‐bound components responsible for translocation into the cytoplasm. In the present study, Avi_5305, an Agrobacterium vitis SBP belonging to Pfam13407, was screened by differential scanning fluorimetry (DSF) and found to be stabilized byd ‐glucosamine andd ‐galactosamine. Avi_5305 is the first protein from Pfam13407 shown to be specific for amino sugars, and co‐crystallization resulted in structures of Avi_5305 bound tod ‐glucosamine andd ‐galactosamine. Typical of Pfam13407, Avi_5305 consists of two α/β domains linked through a hinge region, with the ligand‐binding site located in a cleft between the two domains. Comparisons with Escherichia coli ribose‐binding protein suggest that a cation–π interaction with Tyr168 provides the specificity ford ‐glucosamine/d ‐galactosamine overd ‐glucose/d ‐galactose.